Illustrated C♯ 2010 - Solis, Daniel M. (Daniel Martin) (Expert's voice in .NET., 2010)
A guide to the C♯ programming language covers such topics as syntax, classes and objects, exception handling, strings, arrays, delegates, threading, and generics.